Cocaine Use and Risk of Ischemic Stroke in Young Adults. Issue 4 (April 2016) - Cheng, Yu-Ching; Ryan, Kathleen A.; Qadwai, Saad A.; Shah, Jay; Sparks, Mary J.; Wozniak, Marcella A.; Stern, Barney J.; Phipps, Michael S.; Cronin, Carolyn A.; Magder, Laurence S.; Cole, John W.; Kittner, Steven J.
Abstract : Background and Purpose—: Although case reports have long identified a temporal association between cocaine use and ischemic stroke (IS), few epidemiological studies have examined the association of cocaine use with IS in young adults, by timing, route, and frequency of use. Methods—: A population-based case–control study design with 1090 cases and 1154 controls was used to investigate the relationship of cocaine use and young-onset IS. Stroke cases were between the ages of 15 and 49 years. Logistic regression analysis was used to evaluate the association between cocaine use and IS with and without adjustment for potential confounders. Results—: Ever use of cocaine was not associated with stroke with 28% of cases and 26% of controls reporting ever use. In contrast, acute cocaine use in the previous 24 hours was strongly associated with increased risk of stroke (age–sex–race adjusted odds ratio, 6.4; 95% confidence interval, 2.2–18.6). Among acute users, the smoking route had an adjusted odds ratio of 7.9 (95% confidence interval, 1.8–35.0), whereas the inhalation route had an adjusted odds ratio of 3.5 (95% confidence interval, 0.7–16.9). After additional adjustment for current alcohol, smoking use, and hypertension, the odds ratio for acute cocaine use by any route was 5.7 (95% confidence interval, 1.7–19.7). Of the 26 patients with cocaine use within 24 hours of their stroke, 14 reported use within 6 hours of their event. Conclusions—: Our data are consistent with a causal association between acute cocaine use and risk of early-onset IS. Abstract : Supplemental Digital Content is available in the text.